Potential Role of Sulfur-Containing Antioxidant Systems in Highly Oxidative Environments - Emmanuel Mukwevho; Zané Ferreira; Ademola Ayeleso (Molecules, 2014)
All forms of life maintain a reducing environment (homeostasis) within their cells. Perturbations in the normal redox state can lead to an oxidative environment which has deleterious effects, especially in health. In biological systems, metabolic activities are dependent mainly on mitochondrial oxidative phosphorylation, a metabolic pathway that uses energy released by the oxidation of nutrients to produce ATP. In the process of oxidative phosphorylation, electrons are transferred from electron donors to electron acceptors such as oxygen in redox reactions and often results to the generation of reactive species. Reactive oxygen species consist of a class of radical and non-radical oxygen derivatives. The imbalance between the reactive oxygen species and antioxidant defence systems leads to oxidative burden and hence, damage biological molecules. Antioxidants help to prevent or fix the deleterious effects of reactive species. Sulfur is an important element in biological systems. This atom is usually integrated into proteins as the redox-active cysteine residue and in molecules such as glutathione, thioredoxin and glutaredoxin which are vital antioxidant molecules and are therefore essential for life. This review covers the role of sulfur containing antioxidant systems in oxidative environments.